2014
DOI: 10.1155/2014/692323
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Study of Common Rigid Steel Connections under the Effect of Heat

Abstract: One of the most important members of steel structure's connection region is beam-to-column connection. Rigid connection in steel moment frame has special role in the behavior of these structures and the fire resistance of these connections can be important. In this paper the behaviors of three common types of rigid connections in Iran under the effect of heat were studied by the use of numerical finite element methods through ABAQUS software. The models were verified by the use of an experimental model through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Li et al [19] studied the mechanical properties of flush end-plate composite joints under the combination of axial loading and elevated temperature conditions. Rahnavard et al [20] studied the behaviors of common types of rigid connections, including connections with an endplate, connections with a bolted cover plate, and bolted T joints, under the effect of heat using numerical FE methods with the ABAQUS software. Fang et al [21] proposed an extended end-plate connection that was formed using shape memory alloy bolts.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [19] studied the mechanical properties of flush end-plate composite joints under the combination of axial loading and elevated temperature conditions. Rahnavard et al [20] studied the behaviors of common types of rigid connections, including connections with an endplate, connections with a bolted cover plate, and bolted T joints, under the effect of heat using numerical FE methods with the ABAQUS software. Fang et al [21] proposed an extended end-plate connection that was formed using shape memory alloy bolts.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous two projects, connection and insulation behaviour was temperature independent and modelled in a linear elastic fashion. However, when a certain façade system is exposed to fire: (a) the mechanical properties of connections like stiffness and strength will change significantly [5,6], and (b) the insulation material may be subject to pyrolysis and other types of degradation. Both aspects should be taken into account during the simulation of structures like façades under fire.…”
Section: Introductionmentioning
confidence: 99%
“…However, some experimental investigations indicated that field-welding quality is difficult to control in key parts of the connection, and unexpected brittle failure has often been observed between the weld metal and base metal at the toe of the weld access holes [8,9]. erefore, to improve the assemblability of SRC shear walls with steel boundary elements and steel coupling beams, referring to the advantages of modular prefabricated multistory steel structures [10][11][12][13][14][15][16][17], an innovative modular prefabricated HCW system is presented in this study. is modular prefabricated HCW system is composed of two SRC walls with steel boundary elements coupled using a full-bolt-connected modular steel coupling beam, and the modules can be assembled rapidly without being welded on site.…”
Section: Introductionmentioning
confidence: 99%